The effect of sublethal concentrations of malathion on some biological parameters of the ectoparasitoid wasp, Habrobracon hebetor (Say, 1836) - Amin ASADI; Jaber KARIMI; Habib ABBASIPOUR (Acta Agriculturae Slovenica)
The ectoparasitoid wasp, Habrobracon hebetor (Say, 1836) (Hym.: Braconidae) is one of the most important natural enemies of many pests in Iran. In this study, the effects of sublethal concentrations of malathion (LC10 and LC25) on biological parameters of the adult wasp including parasitism percentage, male production and longevity of the parasitoid in different growth stages (larvae, pupae and adult) were investigated. The experiments were conducted at 26 ± 1 °C, 60 ± 5 % RH, and 16L:8D h photoperiods. The effect of sublethal concentrations of malathion on adults was determined by exposure of wasp to insecticide, and in the case of larvae and pupae, immersion method was used. Based on the results, with the increase of toxic dose, the percentage of parasitism in adult decreased from 95.6 5% to 87.78 %, compared to the control treatment. Male production increased from 22.73 % in control to 56.38 % at LC25 concentration. Also, the percentage of parasitism of the malathion-impregnated wasp larvae decreased from 87.78 to 22.92%, compared to the control treatment. Male production from 30.94 % in the control increased to 39.63 % at the LC25 concentration. In addition, the percentage of parasitism in the wasp pupae impregnated with malathion was reduced from 93.33 to 88.89 %, respectively. Male production increased from 22.98 in the control to 37.23 % in the LC25 concentration. The data showed that pupae were more susceptible to sublethal concentrations than the larvae.